Perception of the elderly about the caregiver's orientations about drug therapy (Research, Society and Development, 2022)
Introduction: the aging of the Brazilian population is a real phenomenon, requiring specific care from health services and family members, in this context, the caregiver assumes a prominent role, especially in relation to the care provided in relation to the singularities of this phase, specific procedures and drug therapies, and the effective support of the latter is closely related to the guidance provided by the caregiver. Objective: to know the perception of the elderly about the guidance received from the caregiver about drug therapy. Methodology: this is a study with a qualitative approach using a semi-structured interview with two guide questions applied to ten elderly people in the area of coverage of a Basic Health Unit located in a municipality in the northern region of the state of Minas Gerais. Results: the caregiver presents himself as an important actor in the care of the elderly, in the face of the senescence process installed, especially in relation to drug therapy. Conclusion: this study showed that the perception of the elderly about the caregiver's orientations in drug therapy is mainly related to a question of dependence on the caregiver, focusing on schedules, Cuidado de Enfermería.